An Experimental Investigation on Effect of High Temperatures on Steel - Chaitanya, Bolishetti; Sunil Pratap Reddy, S; Karthik, Muchakurthi (International Journal of Computer Sciences and Engineering, 2025)
The behaviour of RC beam and column members at elevated temperatures are being studied experimentally andanalytically widely. However, hardly any attention is given towards analyzing the behaviour of structures with SFRC, e.g. SFRC beams, columns, portal frame etc. exposed to fire. Herein, is a paper research to study the impact of fire on steel reinforcement in reinforce concrete structures at elevated temperature that analyzed by means of a three dimensional (3D) nonlinear transient thermo-mechanical finite element (FE) analysis and validated with commercially software ANSYS and SAFIR.